Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Perbankan Syariah - Zulfikri Charis Darmawan; Ahmad Ajib Ridlwan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
Increasing customer satisfaction is a demand that must be implemented, because by increasing customer satisfaction then the existence of Islamic banking can be maintained. Although the level of competition sharia financial institutions are also getting tighter. One of the instruments that can increase customer satisfaction is the quality of banking services.This research is quantitative research which aims to know how big influence of service quality of bank to customer satisfaction at BTN Syariah Kc Surabaya. From the results of research conducted with independent variables of quality of banking services with indicators of physical evidence, reliability, responsiveness, assurance, empathy, sharia compliance. Through incidental sampling technique with 100 respondents and questionnaire distribution method can be concluded that the quality of banking services in BTN Syariah Kc Surabaya as a whole affects customer satisfaction.